Perencanaan Program Keunggulan melalui Dunia Industri dan Dunia Kerja (IDUKA) SMK Negeri Pertanian Pembangunan Cianjur - H. Soro, Suharyanto; Dariah, Dinar; Prasetiawati, Eka; Jamilah, Nina (LP. Ma'arif Janggan Magetan, 2024)
Educational units carry out short-term, medium-term, and long-term planning in order to achieve their goals. Planning is not a simple activity. This is because its formulation requires an understanding of the alignment with the vision and mission of the educational unit. Planning that has been prepared does not always run according to previous provisions. This study aims to describe the planning of the Center of Excellence Vocational School program through the Industrial World and the World of Work so that graduates are competent in their fields. The researcher used a qualitative research method. Meanwhile, the data collection method used observation, interview, and documentation study methods. Sample selection was carried out by purposive sampling. In other words, the samples in this study were the principal, teachers, and students. The research activities were carried out in the 2024 academic year. The results of the study showed: (1) SMKN PP Cianjur has prepared eight programs (planning); (2) SMKN PP Cianjuar collaborates with IDUKA; (3) The positive impact of the Center of Excellence Vocational School program is the creation of competent graduates who are accepted in the world of work.